2010
DOI: 10.1038/leu.2010.225
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1-induced autophagy promotes chemotherapy resistance in leukemia cells

Abstract: Autophagy, a tightly regulated lysosome-dependent catabolic pathway, is important in the regulation of cancer development and progression and in determining the response of tumor cells to anticancer therapy. However, the role of autophagy in leukemia still remains largely unknown. Here we show that high-mobility group box 1 (HMGB1), the best characterized damage-associated molecular pattern, was released from leukemia cell lines after chemotherapy-induced cytotoxicity and activated autophagy to protect against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
203
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(213 citation statements)
references
References 47 publications
8
203
1
1
Order By: Relevance
“…The prototypical damage-associated molecular pattern molecule (DAMP) (45), HMGB1 is released with sustained autophagy (22,23,40,41,47), late apoptosis (1), and necrosis (34). Consistently, HMGB1 was released by pancreatic cancer cells (Panc2.03, Panc02, and Panc1.28) during oxidative injury (Fig.…”
Section: Upregulation Of Rage Expression In H 2 O 2 -Induced Oxidativsupporting
confidence: 51%
“…The prototypical damage-associated molecular pattern molecule (DAMP) (45), HMGB1 is released with sustained autophagy (22,23,40,41,47), late apoptosis (1), and necrosis (34). Consistently, HMGB1 was released by pancreatic cancer cells (Panc2.03, Panc02, and Panc1.28) during oxidative injury (Fig.…”
Section: Upregulation Of Rage Expression In H 2 O 2 -Induced Oxidativsupporting
confidence: 51%
“…[50][51][52][53] Delivery of exogenous HMGB1 protein to cells triggers autophagy or apoptosis in cancer cells, depending on its redox status and receptors. Reducible HMGB1 (i.e., where the cysteines are not terminally oxidized) binds to the receptor for advanced glycation end products (RAGE), induces Beclin 1-dependent autophagy, and promotes pancreatic or colon tumor cell line resistance to chemotherapeutic agents and ionizing radiation.…”
Section: Other Beclin 1-binding Proteins In Autophagymentioning
confidence: 99%
“…CML cells expressing BCR/ABL oncoprotein at high levels were shown to induce autophagy in order to recover from targeted and nontargeted treatment options, indicating the protective effect of autophagy in CML [109]. These findings are supported by another recent report that indicated that the release of specific damage-associated molecular pattern molecules (DAMPs) after chemotherapy conferred drug resistance to leukemic cells by activating the autophagic pathway [110,111]. In addition to these findings, B-cell CLL was also shown to develop resistance to the tyrosine kinase inhibitor dasatinib by activating autophagy [112] In another report, overexpression of the melanoma differentiation-associated gene-7/interleukin-24 (mda-7/IL-24) was shown to induce autophagy and confer survival advantage to leukemic cells [113].…”
Section: Importance Of Autophagy In Leukemic Cell Survival and Drug Rmentioning
confidence: 56%